Design and Development of Web-Based E-Learning System Using Waterfall for Evaluation - Rahardian Septianto; Ari Hidayatullah (Journal of Information Systems and Technology Research, 2025)
The learning evaluation process at SMK Assyafi’iyah 02 still encounters fundamental challenges, including the absence of an integrated digital system, reliance on manual distribution of questions and answers, frequent delays in score recapitulation, and limited transparency between teachers and students. These conditions often result in inefficiency, data inaccuracy, and difficulties in monitoring students’ academic progress in real time. The research problem addressed in this study is how to design and implement a web-based e-learning application that is able to overcome these obstacles and support more effective evaluation. Therefore, the purpose of this study is to build an information system that integrates exam management, online submission, automated scoring, manual correction, a nd role-based access, with the goal of improving the speed, accuracy, and transparency of learning evaluations. This study applies the Waterfall development method consisting of requirement analysis, system design, implementation, and testing to ensure a structured and systematic process. The contribution of this research lies in providing a practical digital platform for schools that have not yet fully adopted e-learning systems, while the novelty is reflected in the integration of evaluation, communication, and monitoring features specifically adapted to the learning context of vocational schools. The testing results show that the system developed is able to reduce evaluation time, improve data accuracy, and provide better accessibility for both teachers and students.